Pengaruh Tanggung Jawab Sosial Perusahaan Terhadap Kinerja Perusahaan Dengan Variabel Pemoderasi Ukuran Perusahaan - Lestari, Hanifah; Istianingsih, Istianingsih; Mukti, Aloysius Harry; Rattanakul, Pimchanok (Journal of Economics and Management, 2024)
This research aims to examine Corporate Social Responsibility on Company Performance Moderating Company Size. The population in this research is all Industrials Sector companies listed on the Indonesia Stock Exchange 2019-2022. The variables used in this research are Company Performance as the dependent variable; Corporate Social Responsibility as an independent variable; and Company Size as a moderating variable. The sampling technique used was the purposive sampling method and a sample of 48 companies was obtained. The analysis methods used are Descriptive Statistical Analysis, Classical Assumption Test, Correlation Test, Multiple Linear Regression Test, and Hypothesis Test. The research results show that Corporate Social Responsibility has a positive effect on Company Performance. As well as Company Size as a moderating variable which cannot moderate the relationship between Corporate Social Responsibility and Company Performance.